2012
DOI: 10.1371/journal.pone.0050391
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor (G-CSF) Protects Oligpdendrocyte and Promotes Hindlimb Functional Recovery after Spinal Cord Injury in Rats

Abstract: BackgroundGranulocyte colony-stimulating factor (G-CSF) is a protein that stimulates differentiation, proliferation, and survival of cells in the granulocytic lineage. Recently, a neuroprotective effect of G-CSF was reported in a model of cerebral infarction and we previously reported the same effect in studies of murine spinal cord injury (SCI). The aim of the present study was to elucidate the potential therapeutic effect of G-CSF for SCI in rats.MethodsAdult female Sprague-Dawley rats were used in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 37 publications
2
45
1
Order By: Relevance
“…12 In this study, G-CSF induced rapid recovery of motor functions in developing compression myelopathy ( Figures 6, 7), and inhibited apoptotic cell death in the anterior horn in chronic cervical cord compression (Figures 5a, b). These findings suggest that G-CSF can act directly on neurons and oligodendrocytes in the spinal cord.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…12 In this study, G-CSF induced rapid recovery of motor functions in developing compression myelopathy ( Figures 6, 7), and inhibited apoptotic cell death in the anterior horn in chronic cervical cord compression (Figures 5a, b). These findings suggest that G-CSF can act directly on neurons and oligodendrocytes in the spinal cord.…”
Section: Discussionsupporting
confidence: 50%
“…The pleiotropic mechanisms of the beneficial effects of G-CSF in acute spinal cord injury include promotion of migration of bone marrow-derived cells, 19 induction of proliferation of oligodendroglial precursors, 20 inhibition of apoptotic cell death, [12][13][14][15] angiogenesis, 21 and suppression of inflammatory cytokines. 12 In this study, G-CSF induced rapid recovery of motor functions in developing compression myelopathy ( Figures 6, 7), and inhibited apoptotic cell death in the anterior horn in chronic cervical cord compression (Figures 5a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats in the vehicle group received an equivalent volume of normal saline at the same time points. We followed the drug-administration regimen described in our previous report of our rat model of SCI [10]. On the day following the final administration of G-CSF, peripheral blood samples were collected for leukocyte counts.…”
Section: G-csf Treatment and Assessment For Mechanical Allodyniamentioning
confidence: 99%
“…G-CSF was found to protect neurons from ischemia-induced cell death and to promote neurogenesis in a rat model of brain ischemia [7,8]. Recently we reported that G-CSF protects neurons and oligodendrocytes from apoptosis in mouse and rat SCI models [9,10]. Moreover, it was reported that G-CSF attenuates peripheral NeP [11,12].…”
Section: Introductionmentioning
confidence: 97%